(untitled) (Bangladesh Journal of Psychology, 2025)
The research paper was to advance and confirm a psychometric measure on gender role attitude among adults in Bangladesh. The knowledge on the attitudes towards gender roles is essential when applying to enhance equity and societal growth, and a crossculturally defined tool to facilitate the same was required. In the first round, 25 items were produced through a logical way of generating so as to make it content relevant. The 220 purposively chosen adult respondents (both male and female) took the preliminary version of the scale. The face validity was determined by judgment of experts and reaction of participants. Item analysis and exploratory factor analysis (EFA) were the steps involved in the analysis of data to extract the item reduction and factors. Based on EFA, 8 items were retained and loaded on two separate factors which were Mutual Understanding and Equity. Inter-factor calculations were statistically significant and thus conspired with the construct (convergent) validity of the scale. The scale had a good overall reliability (Cronbach α = .82) and one could find that its factors were also relatively reliable with acceptable levels of internal consistency. The use of independent sample t-tests demonstrated important gender based differences in gender role attitudes between the male and female group, and this area of significant perceptual difference has been highlighted. It will be found out that the newly derived scale was in fact reliable as well as valid in measuring gender role attitudes in the Bangladeshi adults. Its high psychometric forms also help the scale become an asset when used in research and social policy interventions in relation to generating gender equity in the future. Bangladesh Journal of Psychology, Vol. 25, December 2025, pp. 1-15